Effect of Coefficient of Variation on Variable Sampling Scheme Indexed in AQL and AOQL under Measurement Error - Uttama Mishra (Communications in Advanced Mathematical Sciences, 2025)
This study investigates the impact of measurement error on variable sampling schemes indexed by Acceptance Quality Limit (AQL) and Average Outgoing Quality Level (AOQL) while considering a known Coefficient of Variation (CV). We present procedures and tables for selecting appropriate variable sampling plans based on specified AQL and AOQL values. In our approach, rejected lots undergo 100% inspection to replace non-conforming items. The operating characteristic (OC) function is analyzed for various CV values, highlighting how measurement error influences the classification of product quality. Our findings emphasize the importance of understanding the relationship between measurement error, CV, AQL, and AOQL in quality control processes, ultimately aiming to enhance product quality and optimize inspection resources.